2014
DOI: 10.1111/cch.12136
|View full text |Cite
|
Sign up to set email alerts
|

Teachers' perceptions about children's movement and learning in early childhood education programmes

Abstract: More training may be required to help early childhood educators use movement experiences to teach academic concepts and improve children's spatial awareness. Future interventions could examine the impacts on children's movement and learning of having teachers move with children during outdoor free play and including more natural features in the design of outdoor play areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 24 publications
4
37
0
2
Order By: Relevance
“…Current research indicates that early childhood care providers experience parent-related barriers to outdoor play but are interested in receiving training to expand outdoor play and increase opportunities for physically active learning (Copeland et al, 2009; Gehris et al, 2015). However, childcare providers’ perceptions of “parent barriers” may be over-emphasized as most parents in this study generally did not endorse the obstacles described by childcare providers in previous studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Current research indicates that early childhood care providers experience parent-related barriers to outdoor play but are interested in receiving training to expand outdoor play and increase opportunities for physically active learning (Copeland et al, 2009; Gehris et al, 2015). However, childcare providers’ perceptions of “parent barriers” may be over-emphasized as most parents in this study generally did not endorse the obstacles described by childcare providers in previous studies.…”
Section: Resultsmentioning
confidence: 99%
“…To our knowledge, no other studies have explored parent perceptions of outdoor play in early learning settings. Several studies have focused on teacher and provider perspectives which concluded that early childhood care providers support the need for outdoor active play to facilitate learning (Copeland, Kendeigh, et al, 2012; Copeland et al, 2009; Gehris, Gooze, & Whitaker, 2015). The results of this study indicate that parents also support outdoor play although parents and childcare providers may not be actively communicating with one another about this topic.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the ways that teachers explain and propose OE activities to children, recognize their natural need to move and experiment and support their attempts, sensorial experiences, and actions in the outdoor context are critical to success (Nelson, 2006; Gehris et al, 2014). However, OE is rarely held as a priority by many teachers (McClintic and Petty, 2015) and they tend to give less time and attention to outdoor activities compared with indoor activities (Wellhousen, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive engagement has a great impact on learning outcomes and this is why it is such considered also in e-learning technology research [15]. Analogously, self-confidence is one of the states that teachers used to monitor children learning outcomes [19].…”
Section: Childrenmentioning
confidence: 99%